Resilience‐oriented service restoration modelling interdependent critical loads in distribution systems with integrated distributed generators. Issue 8 (21st December 2020) - Bajwa, Abdullah Akram; Mokhlis, Hazlie; Mekhlief, Saad; Mubin, Marizan; Azam, Munir Muhammad; Sarwar, Sohail
Abstract: The exponential increase in the frequency and intensity of high impact low probability weather‐related events have pivoted the paradigm of research pertaining to power systems towards resilience. Power system is considered as a critical infrastructure, directly linked to the nation's economy, security and health. Therefore, recent researchers have proposed several techniques to enhance the resilience of power systems. In those techniques, critical loads have been considered independent in nature and different metrics have been proposed to evaluate the resilience of the network. To enhance the resiliency, this paper incorporated distributed generators in the distribution network and critical loads are modelled interdependently. Furthermore, a novel resilience metric is proposed in this paper to evaluate the resilience of a distribution system. The proposed model is formulated as a mixed integer second‐order cone programming problem and the efficacy of the proposed model is evaluated on IEEE 33‐ and 69‐bus systems. The competence of the proposed resilience metric is evaluated after comparison with existing resilience metrics.